064 Effect of six-week exercise training on reducing biomechanical re-injury risk factors of professional female basketball players with anterior cruciate ligament reconstruction during stop jump. (3rd March 2020) - Qiu, Jihong; Shu Hang Yung, Patrick
Abstract : Background: ACL injuries are commonly seen in basketball players, especially in female players. Players with previous ACL injuries would have higher re-injury risk and there is till no standardized training protocol for them to prevent further ACL injury. Objective: To detect the effect of a six-week training program on knee biomechanics during stop jump. Design: Prospective cohort study. Setting: Laboratory setting. Patients (or Participants): Nine young adult (age: 18–24) professional (National second level) female basketball players who had previous ACL reconstruction (post-op: 9 months-2years) and returned to daily training were included in this study. Interventions (or assessment of risk factors): Six-week supervised exercise training consisting of strength, core stability, balance and proprioception, agility and flexibility and plyometric training was implemented in participants' daily training. All participants need to take the exercise 5 times/week. Main outcome measurements: Kinematics and kinetics of both lower extremities during stop-jump task were recorded by VICON before and after the six-week exercise training. Student t-test was used for statistics. Results: After six week training, there is significant decrease in knee internal rotation angle (16.82±27.98 to 11.67±27.38, p<0.05) and greater knee flexion angle (19.73±9.57 to 26.03±9.32, p<0.05) at the initial ground contact on the injured side; it shows greater knee extension torque (-0.99±0.88 to -1.23±0.92, p<0.05) and smaller internal rotation torque (0.02±0.07 to -0.05±0.09, p<0.05) at the peak knee flexion angle on the injured side. On the contralateral side, there is significant decreased knee internal rotation angle (-13.21±6.42 to -5.35±3.93, p<0.05) and valgus angle (-2.16±3.83 to 0.09±3.10, p<0.05) at the initial ground contact. Conclusions: The six-week training program could modify biomechanical properties associated with ACL injury, which indicates that it has potential effect in reducing ACL re-injury risk in professional female basketball players.